A rare case of salivary gland tumor mimicking vascular malformation in the retromandibular region - Megha M George; Vijaylaxmi B Madalli; Lijoy Abraham; Kirty Nandimath (Wolters Kluwer Medknow Publications, 2023)
Mucoepidermoid carcinoma (MEC) of the accessory salivary glands is a rare occurrence, accounting for less than 5% of head and neck cancers and 10% of all salivary gland tumors. In this article, we report a case of MEC with a unique clinical presentation mimicking a vascular malformation. It is very uncommon to find a MEC in the retromolar region. The patient was a 21-year-old male who had noticed a swelling in his mouth for 4 years. It was clinically diagnosed as a vascular malformation, and later radiographic evaluations affirmed the fact that it was a tumor arising from the minor salivary glands. The patient underwent surgery in a private hospital, with no signs of recurrence postoperatively.